Correlation between Clinical Prognostic Factors and CAP Patients’ Output due to Klebsiella Pneumoniae - Handriyani,; Wulandari, Laksmi (International Journal of Psychosocial Rehabilitation, 2020)
Background: Infections of K. pneumoniae are often thought to be associated with higher mortality rates; this etiology has not been proven to be a clinical prognostic factor of death.Objectives: to evaluate the relationship between age, sex, delay of antibiotic administration, smoking status, hemoglobin, albumin, Chronic Obstructive Pulmonary Disease (COPD), diabetes mellitus (DM), cardiovascular disease, Patients Outcome Research Team (PORT) score, antibiotic resistance, extended-spectrum β-lactamase (ESBL) strain through treatment length, ICU admission indication, and mortality of community-acquired pneumonia (CAP) patients caused by K. pneumoniae.Method: The CAP patients infected with K. pneumoniae in the male and female pulmonology room of Dr. Soetomo General Hospital, Surabaya, Indonesia, from 1 January 2009 to 31 December 2012 were analyzed in a retrospective cohort. Observed outcomes included treatment length, ICU admission indication, and mortality.Result: The sample size fulfilling the inclusion was 41 patients. There was a significant correlation between comorbid COPD (10.000 OR, p = 0.018), DM (0.714 OR, p = 0.040), and PORT score (1.471 OR; p = 0.014) through ICU outpatient indications. In multivariate analysis, comorbid COPD (p = 0.013) was the most dominant independent factor through ICU indication care, whereas albumin (p = 0.040) and ESBL germs (p = 0.027) were the same dominant independent factors for mortality.Conclusion: There was a relationship between comorbid COPD, DM, and PORT score on ICU indication care in univariate analysis.